Graphite-silicon-based composite negative electrode material and preparation method thereof

By using graphite-silicon-based composite negative electrode material in lithium-ion batteries, the SiOx/C composite layer is used to alleviate volume expansion stress, and the specific capacity and cycle stability of the battery are improved, and the low graphite negative electrode capacity and silicon negative electrode in lithium-ion batteries are solved. The expansion problem has achieved the improvement of high energy density and rate performance.

CN119181786AInactive Publication Date: 2024-12-24NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411262156.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Among the existing lithium-ion batteries, the theoretical specific capacity of graphite negative electrode is lower, and the electrode structure ruptures due to volume expansion, which limits the improvement of the energy density and cycle stability of the lithium-ion battery.

Method used

Using graphite-silicon-based composite negative electrode material, the SiOx/C composite layer is formed on the graphite surface, and the SiOx/C layer is converted into amorphous carbon uniformly distributed SiOx/C layer to improve conductivity and alleviate the mechanical stress caused by volume expansion, forming G @SiOx/C composite anode material.

Benefits of technology

It significantly improves the specific capacity, rate performance and cycle stability of lithium-ion batteries, overcomes the shortcomings of traditional physical blending and chemical modification methods, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181786A_ABST
    Figure CN119181786A_ABST
Patent Text Reader

Abstract

The invention discloses a graphite-silicon-based composite negative electrode material which comprises graphite and a SiOx / C composite layer coated on the surface of the graphite. The invention also discloses a preparation method of the graphite-silicon-based composite negative electrode material, which comprises the following steps: (1) dispersing graphite and hexadecyl trimethyl ammonium bromide into an aqueous solution of ethanol, and uniformly stirring; (2) adding ammonia water into the solution in the step (1), uniformly mixing, then adding organosilane, and sealing and stirring at room temperature; (3) centrifuging the reacted solution, and cleaning and drying the centrifuged solid to obtain an initial product; and (4) performing high-temperature carbonization on the initial product in an argon protection atmosphere to obtain the graphite-silicon-based composite negative electrode material of which the graphite surface is coated with a SiOx / C composite layer. The composite material prepared by the invention has relatively high specific capacity, excellent rate capability and cycling stability when being used as a lithium ion battery negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a graphite-silicon based composite negative electrode material and also relates to a method for preparing the composite negative electrode material. Background Art

[0002] With the rapid development of electric vehicles, portable electronic devices, and renewable energy, lithium-ion batteries have become one of the indispensable energy storage devices in people's lives. In the past few decades, graphite has been used as the main negative electrode material for lithium-ion batteries due to its excellent cycle stability. However, the low theoretical specific capacity of graphite negative electrode (372mAh / g, LiC 6 ) seriously limits the further improvement of the energy density of lithium-ion batteries.

[0003] Silicon anode has a very high theoretical capacity (4200mAh / g, Li 4.4 Si) and abundant reserves have become the first choice for the negative electrode material of the next generation of lithium-ion batteries. However, the huge volume expansion during the lithium insertion process will cause the electrode structure to break or even fall off, which will eventually lead to a sharp deterioration of the electrochemical performance, seriously restricting the large-scale application of pure silicon negative electrodes. At present, the use of silicon negative electrodes mixed with graphite has become the mainstream solution to solve the above problems.

[0004] Existing blending technologies mainly include two methods: physical blending and chemical modification. Physical blending is to directly mix silicon-based materials and graphite. This method is relatively simple, such as ball milling. However, this method has significant defects. First, the problem of volume expansion of silicon particles during charging and discharging has not been solved. The stress generated by the expansion may destroy the relatively stable interface of graphite, resulting in a decrease in the overall performance of the battery, which is even worse than a single graphite negative electrode. In addition, physical blending makes it difficult to achieve precise control of material morphology and structure, and the repeatability is poor. Therefore, the physical blending method is not good at dealing with silicon volume expansion and interface stability, making it difficult to be widely used in practice.

[0005] Vapor deposition (CVD) is a commonly used chemical modification technology that improves the performance of the negative electrode by depositing a thin film on the surface of the negative electrode material. Although the CVD method can more accurately control the deposition thickness and uniformity of the thin film, the method usually needs to be carried out at high temperatures (above 900°C), which not only increases energy consumption and costs, but also brings safety risks. In addition, the CVD method has expensive equipment and complex processes, which is not suitable for large-scale industrial production. Other methods such as thermochemical pyrolysis and spray drying also face similar dilemmas. Summary of the invention

[0006] Purpose of the invention: The purpose of the present invention is to provide a graphite-silicon-based composite negative electrode material, which, on the one hand, can effectively improve the energy density and rate performance of the battery and overcome the problem of low specific capacity of the graphite negative electrode; on the other hand, it can greatly improve the cycle stability of the battery; another purpose of the present invention is to provide a method for preparing the above-mentioned composite negative electrode material.

[0007] Technical solution: The graphite-silicon-based composite negative electrode material of the present invention comprises graphite and SiO coated on the surface of the graphite. x / C composite layer.

[0008] Among them, graphite has a two-dimensional flake structure.

[0009] Among them, graphite and SiO coated on the graphite surface x The mass ratio of the / C composite layer is 8.6~9:1~1.4.

[0010] Among them, SiO x In the SiO / C composite layer, x and C are homogeneously distributed.

[0011] The SiO in the present invention x The / C composite layer is converted from organosilicon. During the carbonization process, the organic groups in the organosilicon will be converted into amorphous carbon and evenly distributed in the silicon-oxygen-silicon network. On the one hand, it can increase the SiO x On the other hand, amorphous carbon as a flexible carbon layer can alleviate the SiO x The mechanical stress caused by volume expansion and contraction during the charging and discharging process enhances the structural stability of the negative electrode material during the charging and discharging process.

[0012] The method for preparing the above-mentioned graphite-silicon-based composite negative electrode material comprises the following steps:

[0013] (1) dispersing graphite and hexadecyltrimethylammonium bromide in an aqueous solution of ethanol and stirring uniformly;

[0014] (2) adding aqueous ammonia to the solution of step (1), mixing well, then adding organosilane thereto, and sealing and stirring at room temperature;

[0015] (3) After the reaction is completed, the solution is centrifuged to obtain a solid (black solid), and the solid is washed and dried to obtain a primary product (a composite of organic silicon-coated graphite, in which organic silane is hydrolyzed and condensed to form organic silicon coated on the graphite surface);

[0016] (4) The primary product is carbonized at high temperature under an argon protective atmosphere to obtain a graphite surface coated with SiO x / C composite layer of graphite-silicon based composite negative electrode material.

[0017] Wherein, in step (1), the mass ratio of graphite to hexadecyltrimethylammonium bromide is 5-50:6-60.

[0018] Wherein, in step (1), the volume ratio of ethanol to water in the ethanol aqueous solution is 0.1 to 5:1.

[0019] Wherein, in step (2), after adding ammonia water, the concentration of ammonia water in the system is 0.1 to 1 mol / L; and the stirring time is 10 to 30 min.

[0020] In step (2), the organosilane is vinyltriethoxysilane or mercaptopropyltrimethoxysilane.

[0021] After the organosilane is added, the concentration of the organosilane in the reaction system is 0.05 to 0.5 mol / L, preferably 0.1 mol / L, and the stirring reaction time is 12 to 36 hours.

[0022] Wherein, in step (4), the sintering temperature is 800-1000° C., and the sintering time is 2-4 hours.

[0023] The present invention adopts a sol-gel method to form a layer of organic silicon coating on the graphite surface, and obtains G@SiO x / C composite negative electrode. On the one hand, SiO x / C composite layer can effectively protect the graphite interface, reduce the occurrence of side reactions, and improve the interface stability and battery cycle life; on the other hand, SiO x The layered coating structure of SiO / C can effectively relieve its own volume expansion stress, reduce the cracking and shedding of the negative electrode material, and improve the mechanical stability of the composite negative electrode material. x / C itself contributes to capacity while providing a good ion transport path, thereby improving the energy density and rate performance of the battery.

[0024] Optimization effect: Compared with the prior art, the present invention has the following significant advantages: the method of the present invention can effectively overcome the defects of the traditional physical blending or chemical modification methods of graphite and silicon-based materials, and the prepared composite material exhibits higher battery specific capacity, excellent rate performance and cycle stability when used as a negative electrode material for lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The present invention provides a process for preparing the composite negative electrode material;

[0026] Figure 2 This is the XRD pattern of the composite negative electrode material obtained in Example 1;

[0027] Figure 3 This is the Raman spectrum of the composite negative electrode material obtained in Example 1;

[0028] Figure 4 This is the high-resolution XPS measurement spectrum of the composite negative electrode material obtained in Example 1 on Si2p;

[0029] Figure 5 Thermogravimetric spectrum of the composite negative electrode material obtained in Example 1;

[0030] Figure 6 This is a SEM image of the composite negative electrode material obtained in Example 1 and the graphite used;

[0031] Figure 7 This is an energy spectrum analysis diagram of the composite negative electrode material obtained in Example 1;

[0032] Figure 8 This is an energy spectrum analysis diagram of the cross section of the composite negative electrode material obtained in Example 1;

[0033] Fig. 9 The rate performance of the composite negative electrode material obtained in Example 1 and the graphite negative electrode ( Fig. 9 a) Cycle performance ( Fig. 9 b) and the charge and discharge curves ( Fig. 9 c, d);

[0034] Fig.10 The cycle performance of the composite negative electrode material obtained in Example 1 and the graphite negative electrode after being assembled into a full battery;

[0035] Fig.11 This is an energy spectrum analysis diagram of the composite negative electrode material obtained in Example 2;

[0036] Fig.12 This is a comparison chart of the rate performance of the composite negative electrode material obtained in Example 2 and the graphite negative electrode. DETAILED DESCRIPTION

[0037] Example 1

[0038] The method for preparing the graphite-silicon based composite negative electrode material of the present invention comprises the following steps:

[0039] (1) 500 mg of graphite and 600 mg of cetyltrimethylammonium bromide (CTAB) were uniformly dispersed in a mixture of 40 mL of anhydrous ethanol and 10 mL of deionized water;

[0040] (2) adding 0.5 mL (25-28 wt.%) aqueous ammonia to the solution of step (1), and stirring the mixture in a sealed container at room temperature for 0.5 h;

[0041] (3) adding 1.0 mL of vinyltriethoxysilane to the solution of step (2) and sealing the reaction at room temperature for 24 h;

[0042] (4) centrifuging the solution after the reaction in step (3), washing the solid after centrifugation, and drying at 60° C. for 12 h to obtain a black powder;

[0043] (5) The black powder obtained in step (4) was sintered at 800° C. for 3 h under an argon atmosphere to obtain a graphite surface coated with SiO x / C composite layer of composite negative electrode material.

[0044] The synthesis mechanism of composite negative electrode materials is as follows Figure 1 First, graphite and organosilane are dispersed in an alcohol-water system. Under the catalytic action of ammonia water, the organosilane undergoes a hydrolysis-condensation reaction and is coated on the graphite surface. Finally, it is carbonized at high temperature in an argon atmosphere to obtain SiO coated on the graphite surface. x / C composite layer of black negative electrode material.

[0045] The XRD spectrum of the G@SiOx / C composite negative electrode material prepared in Example 1 is as follows: Figure 2 As shown, the material mainly corresponds to the characteristics of graphite, showing the characteristic diffraction peak of graphite with the (002) peak as the main peak, while the characteristic peak of silicon is not observed, indicating that the coating structure presents amorphous characteristics in the material.

[0046] like Figure 3 As shown in the graphite surface coated with SiO x In the Raman spectra of the / C composite structure before and after coating, the I D / I G The ratio is significantly increased, and the 2D peak is significantly weakened and broadened, indicating that the coating layer introduces stress or structural defects, affecting the orderly crystal structure of the graphite surface, proving the conclusion that the above-mentioned coating shell is mainly an amorphous silicon-oxygen / carbon composite structure. Figure 4 In the XPS spectrum shown, by separating the peaks of Si spectrum, it can be seen that its valence state is between divalent silicon and tetravalent silicon. Figure 5 The thermogravimetric analysis (TGA) diagram shown in Figure 1 shows that the G@SiO x SiO in C / C composites x The content is 13.19% of the total mass of the composite material.

[0047] contrast Figure 6 The SEM images shown in a and 6b show that an obvious coating layer appears on the graphite surface. x / C particle size is about 10μm, Figure 7 From the EDS elemental analysis signals, it can be seen that the three elements of silicon, oxygen and carbon are evenly distributed on the surface of the particles. Figure 8 The G@SiO xThe cross-sectional mapping of the C particles shows that the silicon signal inside the particles is obviously missing, proving that SiO x / C is coated on the graphite surface.

[0048] Application of the material prepared in Example 1 as negative electrode material for lithium-ion batteries:

[0049] The preparation process of the electrode sheet adopts G@SiO x / C composite material as active material, Super-p as conductive agent, PVDF as binder; the mass ratio of active material, conductive agent and binder is 8:1:1. The active material and conductive agent are fully mixed in proportion and ground evenly, and PVDF NMP solution is added in proportion and fully ball-milled; finally, the mixture slurry is evenly coated on copper foil, vacuum dried at 90℃ for 12h, and then punched into 12mm circular electrode sheets. With 1mol / L LiPF 6 EC / DMC / DEC (volume ratio of 1:1:1) solution was used as the electrolyte and Celgard 2500 separator was used to assemble CR2016 button cells in a glove box.

[0050] On the LAND battery test system (LAND CT2001A), 0.01~1.5V (vs Li / Li + ) operating voltage range for charge and discharge tests. The full battery test uses NCM811 as the positive electrode material and 1 mol / L LiPF 6 EC / DMC / DEC (volume ratio of 1:1:1) solution was used as the electrolyte. On the LAND battery test system (LAND CT2001A), 3.0~4.2V (vs Li / Li + ) working voltage range for charge and discharge test.

[0051] Fig. 9 b is G@SiO x Comparison of the cycling performance of G@SiO / C composites and graphite as negative electrode materials for lithium-ion batteries. x The / C composite material has a first-cycle charge and discharge capacity of 707.4 mAh / g at a current density of 0.05 A / g, and a coulombic efficiency of 64.31%. After two cycles at a current density of 0.05 A / g and 300 cycles at a current density of 0.2 A / g, it still maintains a specific capacity of 395 mAh / g, which exceeds the theoretical specific capacity of traditional graphite negative electrode (372 mAh / g), showing its good cycle stability and effective improvement of energy density. Fig. 9 a and Fig. 9 c. Fig. 9 d is G@SiO xThe rate performance comparison between G@SiO / C composites and graphite as negative electrode materials for lithium-ion batteries shows that x After one cycle at a current density of 0.1A / g, the discharge specific capacity of the / C composite material was 440.3, 378.9, 262.4, 186.0, 160.2, and 151.5 mAh / g at current densities of 0.1, 0.2, 0.4, 0.6, 0.8, and 1.0A / g, respectively. When the current density was restored to 0.1A / g, the discharge specific capacity was restored to 447.7 mAh / g, showing good rate performance.

[0052] Fig.10 G@SiO x The cycling performance of the full battery assembled with the NCM811 positive electrode and the / C composite material as the negative electrode shows that the specific capacity of the full battery always exceeds 140 mAh / g in 300 cycles, and the capacity retention rate after 300 cycles is 96.81%, showing excellent cycling performance compared with the graphite negative electrode that has not been tested.

[0053] The above results show that the G@SiO x / C composite materials have excellent cycle performance, rate performance and excellent full battery performance. They are potential application materials for optimizing and modifying traditional graphite negative electrodes at low cost and achieving long cycle life and high specific capacity lithium-ion batteries.

[0054] Example 2

[0055] The method for preparing the graphite-silicon based composite negative electrode material of the present invention comprises the following steps:

[0056] (1) 500 mg of graphite and 600 mg of cetyltrimethylammonium bromide (CTAB) were uniformly dispersed in a mixture of 40 mL of anhydrous ethanol and 10 mL of deionized water;

[0057] (2) adding 0.5 mL (25-28 wt.%) aqueous ammonia to the solution of step (1), and stirring the mixture in a sealed container at room temperature for 0.5 h;

[0058] (3) adding 1.0 mL of vinyl triethoxy silane to the solution of step (2), and sealing and reacting for 12 h at room temperature; then adding 1.0 mL of vinyl triethoxy silane again, and sealing and reacting for 12 h;

[0059] (4) centrifuging the solution after the reaction in step (3), washing the solid after centrifugation, and drying at 60° C. for 12 h to obtain a black powder;

[0060] (5) The black powder obtained in step (4) was sintered at 800° C. for 3 h under an argon atmosphere to obtain a graphite surface coated with SiO x / C composite layer of composite negative electrode material.

[0061] Fig.11 The thermogravimetric analysis (TGA) diagram shown in Figure 2 shows that the G@SiO x SiO / C composites x The content is 27.11%. x The electrode was prepared from the 1.5-1.5-methylenediaminetetraacetic acid (ETA) / C composite material and subjected to electrochemical testing. The electrode preparation method, assembly and testing conditions were the same as those in Example 1.

[0062] Through testing, the material was tested for rate performance at different current densities of 0.1, 0.2, 0.4, 0.6, 0.8, and 1.0 A / g after one cycle at a current density of 0.1 A / g. It can be seen that the discharge capacity can reach 433.2, 383.9, 295.3, 237.7, 197.6, and 175.7 mAh / g, respectively. When the current density returns to 0.1 A / g, the discharge capacity recovers to 428 mAh / g. Fig.12 shown.

[0063] Example 3

[0064] The preparation method of Example 3 is the same as that of Example 1, except that 0.5 mL of vinyltriethoxysilane is added in step (3). x / C composite material to prepare electrodes for electrochemical testing. The electrode preparation method, assembly and testing conditions are the same as in Example 1.

[0065] Through testing, it was found that the material had an initial discharge capacity of 594.5 mAh / g at a current density of 0.05 A / g. After two cycles at a current density of 0.05 A / g and 300 cycles at a current density of 0.2 A / g, the capacity could still maintain a reversible capacity of 347.5 mAh / g.

[0066] Example 4

[0067] The preparation method of Example 4 is the same as that of Example 1, except that 1.0 mL (25-28 wt.%) of aqueous ammonia is added in step (2). x / C composite material to prepare electrodes for electrochemical testing. The electrode preparation method, assembly and testing conditions are the same as in Example 1.

[0068] Through testing, it was found that the material had an initial discharge capacity of 476.5 mAh / g at a current density of 0.05 A / g. After two cycles at a current density of 0.05 A / g and 300 cycles at a current density of 0.2 A / g, the capacity could still maintain a reversible capacity of 352.7 mAh / g.

[0069] Example 5

[0070] The preparation method of Example 5 is the same as that of Example 1, except that in step (1), the mixture is composed of 10 mL of anhydrous ethanol and 40 mL of deionized water. x / C composite material to prepare electrodes for electrochemical testing. The electrode preparation method, assembly and testing conditions are the same as in Example 1.

[0071] Through testing, it was found that the material had an initial discharge capacity of 488.4 mAh / g at a current density of 0.05 A / g. After two cycles at a current density of 0.05 A / g and 300 cycles at a current density of 0.2 A / g, the capacity could still maintain a reversible capacity of 376.9 mAh / g.

[0072] Example 6

[0073] The preparation method of Example 6 is the same as that of Example 1, except that 1.0 mL of mercaptopropyltrimethoxysilane is added in step (3). x / C composite material to prepare electrodes for electrochemical testing. The electrode preparation method, assembly and testing conditions are the same as in Example 1.

[0074] Through testing, it was found that the material had an initial discharge capacity of 835.4 mAh / g at a current density of 0.05 A / g. After two cycles at a current density of 0.05 A / g and 300 cycles at a current density of 0.2 A / g, the capacity could still maintain a reversible capacity of 340.5 mAh / g.

[0075] Example 7

[0076] The preparation method of Example 7 is the same as that of Example 1, except that the sintering temperature in step (5) is 900°C. x / C composite material to prepare electrodes for electrochemical testing. The electrode preparation method, assembly and testing conditions are the same as in Example 1.

[0077] Through testing, it was found that the material had an initial discharge capacity of 584.2 mAh / g at a current density of 0.05 A / g. After two cycles at a current density of 0.05 A / g and 300 cycles at a current density of 0.2 A / g, the capacity could still maintain a reversible capacity of 356.3 mAh / g.

[0078] Example 8

[0079] The preparation method of Example 8 is the same as that of Example 1, except that no ammonia water is added in step (2). Since ammonia water acts as a catalyst in the preparation, the organosilane in this example cannot be hydrolyzed and condensed to coat the graphite surface, and G@SiO cannot be obtained. x / C composite material.

[0080] Example 9

[0081] The preparation method of Example 9 is the same as that of Example 1, with the only difference being that the solvent in step (1) is only deionized water, anhydrous and without ethanol. Since the proportion of water in the solution is too high, the hydrolysis and condensation reaction of the organosilane in this example is difficult to proceed, and G@SiO x / C composite material.

[0082] Example 10

[0083] The preparation method of Example 10 is the same as that of Example 1, except that 10 mL of vinyltriethoxysilane is added in step (3). Since the content of the organosilane in this example is too high, the organosilane will self-nucleate to form particles and cannot form a uniform composite material.

Claims

1. A graphite-silicon based composite negative electrode material, characterized in that: Including graphite and SiO coated on the surface of graphite x / C composite layer.

2. The graphite-silicon based composite negative electrode material according to claim 1, characterized in that: The graphite and SiO x The mass ratio of the / C composite layer is 8.6~9:1~1.

4.

3. The graphite-silicon based composite negative electrode material according to claim 1, characterized in that: SiO x In the SiO / C composite layer, x and C are uniformly distributed.

4. The method for preparing the graphite-silicon based composite negative electrode material according to claim 1, characterized in that: The steps include: (1) dispersing graphite and hexadecyltrimethylammonium bromide in an aqueous solution of ethanol and stirring uniformly; (2) adding aqueous ammonia to the solution of step (1), mixing well, then adding organosilane thereto, and sealing and stirring at room temperature; (3) After the reaction is completed, the solution is centrifuged to obtain a solid; The solid matter is washed and dried to obtain a primary product; (4) The primary product is carbonized at high temperature under an argon protective atmosphere to obtain a graphite surface coated with SiO x / C composite layer of graphite-silicon based composite negative electrode material.

5. The method for preparing a graphite-silicon based composite negative electrode material according to claim 4, characterized in that: In step (1), the mass ratio of graphite to hexadecyltrimethylammonium bromide is 5-50:6-60.

6. The method for preparing a graphite-silicon based composite negative electrode material according to claim 4, characterized in that: In step (1), the volume ratio of ethanol to water in the ethanol aqueous solution is 0.1 to 5:

1.

7. The method for preparing a graphite-silicon based composite negative electrode material according to claim 4, characterized in that: In step (2), after adding ammonia water, the concentration of ammonia water in the system is 0.1 to 1 mol / L; and the stirring time is 10 to 30 min.

8. The method for preparing a graphite-silicon based composite negative electrode material according to claim 4, characterized in that: In step (2), the organosilane is vinyltriethoxysilane or mercaptopropyltrimethoxysilane.

9. The method for preparing the graphite-silicon based composite negative electrode material according to claim 8, characterized in that: After the organosilane is added, the concentration of the organosilane in the reaction system is 0.05 to 0.5 mol / L, and the stirring reaction time is 12 to 36 hours.

10. The method for preparing a graphite-silicon based composite negative electrode material according to claim 4, characterized in that: In step (4), the sintering temperature is 800-1000° C. and the sintering time is 2-4 hours.

Citation Information

Patent Citations

  • Method for preparing stratified-structure SiOx difunctional compound negative electrode material for lithium battery

    CN103855376A

  • Negative electrode material, negative electrode pole piece and method for fabricating same

    CN111200123A

  • Method for preparing silicon-carbon negative electrode material by using waste graphite of lithium ion battery

    CN114335495A

  • Graphite-silicon-amorphous carbon composite negative electrode material and preparation method thereof

    CN118448618A

  • Silicon-carbon composite material, method for preparing silicon-carbon composite material, negative electrode sheet, and electrochemical device

    WO2023197097A1